Development of a solar-energy activated organic Rankine-cycle pilot power plant - Bala, Eli Jidere (Cranfield University, 1984)
with the development of a low-grade energy engine in the School of Mechanical Engineering at Cranfield, there began a venture towards utilizing the Sun's power to operate the engine via a thermodynamic cycle, in an Egyptian desert area, i. e latitude 3Q0N. The derived mechanical power is to drive an irrigation pump at the site. The solar thermal system is to operate in a Rankine-cycle using an organic working fluid. The engine is in the form of a multi-vane expander. The solar-energy collector comprises of an array of gravity-assisted heat- pipes each enclosed within a cylindrical high-vacuum glass tube. The irrigation water which is to be sucked from below ground level, is also to cool the shell-and-tube condenser. The first section(i. e. PART A) of this thesis is a presentation of some design optimization concepts in the development of the thermodynamically operated solar-energy system. As in any desert area dust will constitute a problem, reducing the harnessing capability of the collector array. Regular cleaning would therefore be essential. However, cleaning a large array (1000) of such fragile tubes in situ is unlikely to be accomplished without cracks and breakages occurring. This perhaps means that the high-vacuum which is essential for each collectors continued adequate thermal performance could be easily lost. The collectors are also considered expensive. For example, one tube with an effective aperture area of about 0.102ml costs about twenty pounds Sterling. These and the fact that the maximum anticipated working temperature in the organic Rankine-cycle would be about 1201 C, led to the study into a means other than evacuation of reducing thermal losses from the receiver of a flat-plate solar-energy collector in the second section (i. e. PART B). A flat-plate collector employing a simple slatted convection suppression device was studied. It was shown that a flat-plate collector employing an effective convection suppression device and an initial cost of about £1o0/m`would be more cost effective than the evacuated-tube collector, when employed to activate the pilot power plant for operatinq temperaures of (80-X120)° C. The cost per peak watt could be reduced by an average value of about 15% depending upon the'operating temperture. Whereas the break-even time against electricity could be reduced by about 4%. However, the overall efficiency of the power plant could fall by an average value of about 23%, depending upon the operating temperature.